2007
DOI: 10.1111/j.1600-0897.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Spontaneous Abortion. Cooperative Effects of ADA and ACP1 Genetic Polymorphisms

Abstract: The data are in agreement with those expected on the basis of the effects of ACP1 and ADA genetic variability on T-cell receptor activity and suggest a cooperative effect of the two polymorphic systems in the susceptibility/resistance to repeated spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
11
1
1
Order By: Relevance
“…Hence, from a preliminary overview, the results presented in this study are different from those observed for Italian women in whom the ADA*2 allele was associated with a lower risk of RSA 10,11…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Hence, from a preliminary overview, the results presented in this study are different from those observed for Italian women in whom the ADA*2 allele was associated with a lower risk of RSA 10,11…”
Section: Discussioncontrasting
confidence: 99%
“…Because adenosine acts as a hormone that regulates blood flow, neurotransmission and platelet aggregation and is a potent vasodilator,25,26 its presence in the uterus and the placenta could contribute to a reduced rate of early loss of zygotes or fetuses, thus protecting ADA*2 -carrying women against RSA 10,11. This protection may be especially relevant for women older than 35 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and clinical characteristics on the sample have been described in detail elsewhere (5). The women included in this analysis had two or more consecutive abortions.…”
mentioning
confidence: 99%
“…The study of this cohort of women started about 15 years ago. ANA and ACA determination have been performed in all women as previously described (5). Reproductive success was reevaluated at a 5-year follow-up.…”
mentioning
confidence: 99%